A Photographic Guide to Seashore Life in the North Atlantic : Canada to Cape Cod - Sept, J. Duane, 1950- (Book collections on Project MUSE., 2008)
"The tides of the North Atlantic are the world's highest, and they reveal a world of amazing seashore life - from jellies and sea anemones, to clams and crabs, to seaweeds and lichens. With some 300 crisp, vibrant color photographs and brief, precise descriptions, this field guide makes it easier than ever to identify Atlantic seashore life from Canada to Cape Cod. Duane Sept covers more than 225 common intertidal species found on rocky shores, sandy shores, mud beaches, and floating docks, and explains the natural history of these specialized organisms. He also describes tidal habitats, tells how to explore the seashore in a safe and environmentally responsible way, and provides extensive information on some of the best places in the North Atlantic to view seashore life."--Jacket